VENTILATION AS A COMPONENT OF THE ENERGY DYNAMIC BALANCE IN BUILDING - ДЕШКО, В. І.; БІЛОУС, І. Ю.; ГУРЄЄВ, М. В. (Technologies and Engineering, 2024)
Purpose. The research aims to analyze dynamic energy modeling of buildings using EnergyPlus and DesignBuilder software. The primary goal is to assess the energy efficiency, indoor air quality, and energy balance of buildings, taking into account various aspects such as ventilation and dynamic changes in temperature and humidity. Methodology. EnergyPlus and DesignBuilder software were utilized to create detailed dynamic models of buildings. Special attention was given to modeling ventilation and studying the energy balance. Various ventilation modeling algorithms were compared to determine their impact on energy efficiency. Findings. Energy flows in buildings based on dynamic energy balances for the heating period were investigated. A detailed analysis of the influence of ventilation on dynamic energy balances in the studied residential building room was conducted. Originality. This research offers a new perspective on dynamic energy modeling of buildings, expanding knowledge in this field by focusing on ventilation and energy balance aspects. The results contribute significantly to the development of approaches to improve energy efficiency, creating new opportunities for practical applications in engineering design and building operation. Practical value. The obtained results are an important contribution for engineers and designers developing strategies to reduce energy consumption and optimize energy use in buildings. The research can serve as a guide for the practical implementation of dynamic modeling in the planning and operation of buildings to achieve optimal energy efficiency.